Innovation Culture and Social Capital - Lažnjak, Jasminka (2008)
The text deals with the questions how important is the role of innovation supportive culture for innovation on the level of society as at the level of organization and is it possible to delineate which type of culture is supportive and which type is hindering factor for innovation.Norms and values associated with innovation culture along with highly developed social capital are not predominant value system in these countries.
Projekt MZOS
Projekt MZOS
ENG